2021
DOI: 10.21203/rs.3.rs-478437/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and Characterization of a Novel Sm+3 Activated NaCdVO4 Phosphors for Red Emitting Material

Abstract: Sm3+ activated NaCdVO4 phosphors were prepared by the simple solid-state reaction method. X-ray diffraction, dispersive energy (EDS), scanning electron microscope (SEM), infrared as well as photoluminescence (PL) techniques were used to characterize obtained samples. Irregular and non-uniform structures were observed by SEM. EDS spectra confirmed the presence of Na, Cd, V, O and Sm elements in each sample. Uuder 405nm excitation, the NaCd1 − xVO4: xSm (x = 0.01, 0.03 and 0.05) exhibits a bright red emission co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Manganites of structure Ln1-xAxMnO3 (with Ln: rare earths and A: divalent element) have interesting physical properties and enormous technological interest in various fields of application. These intrinsic features are often described in these highly correlated electron systems by the indirect exchange interactions between the Mn 3+ and Mn 4+ ions, the average ionic radius of site A, and the magnetic and orbital disorder [1][2][3][4]. In this structure manganese has a mixed valence Mn 3+ /Mn 4+ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganites of structure Ln1-xAxMnO3 (with Ln: rare earths and A: divalent element) have interesting physical properties and enormous technological interest in various fields of application. These intrinsic features are often described in these highly correlated electron systems by the indirect exchange interactions between the Mn 3+ and Mn 4+ ions, the average ionic radius of site A, and the magnetic and orbital disorder [1][2][3][4]. In this structure manganese has a mixed valence Mn 3+ /Mn 4+ .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the trivalent element is substituted Ln 3+ by a divalent or monovalent element leads to oxidation of the Mn 3+ ions ([Ar] 3d 4 ) into Mn 4+ ions ([Ar] 3d 3 ). The La1-xCaxMnO3 system is one of the most studied compounds in recent years due to its rich magnetic and electrical behavior [5,6]. Previous studies carried out in our laboratory [7,8] on manganites of the perovskite type of general formula La0.5Ca0.5MnO3 substituted by silver in the A site revealed that 10% silver is sufficient to destroy the state charge order and increase ferromagnetic interactions with an increase in TC.…”
Section: Introductionmentioning
confidence: 99%